Microstructures and high-temperature mechanical properties in 9Cr–0.5Mo–1.8W–VNb steel after aging at 650°C. (2nd November 2015) - Guo, X.; Gong, J. M.; Jiang, Y.; Wang, X. W.; Zhao, Y. P.
Abstract : A series of experiments, including post-aged tensile tests, charpy impact tests, Vickers hardness test, scanning electron microscopy (SEM) examinations and transmission electron microscopy (TEM) observations, were carried out to investigate the microstructure evolution and high-temperature mechanical properties of P92 steel. Experimental results show that martensitic lath structure gradually recovers during long-term aging; meanwhile, the content and size of spheroidal M23 C6 together with Laves phase distributed mainly along prior austenite grain boundaries and subgrain boundaries increase with extending the aging time, but MX in grain interior seems to be stable. The strength parameters (σys and σult ), the ductile parameters (δ and Φf ) and high-temperature impact absorbed energy all show an initially slight increase followed by a decrease with the increase of the aging time up to 500 h. After aging for 2000 h at 650°C, this degradation behaviour becomes stable, although the Vickers hardness is not strongly affected by the aging time. Based on the microstructural observations and high-temperature mechanical properties, the strengthening mechanism of P92 steel was discussed.